Rethinking the Connection Between GPA and Self-Regulated Learning: A Study in Indonesian Private Universities - Rizki, Lussy Midani; Kusumah, Yaya Sukjaya (FKIP Universitas Lampung, 2024)
This study investigates the relationship between self-regulated learning (SRL) strategies and academic performance, measured by grade point average (GPA), among undergraduate students at a private university in Indonesia. Using a quantitative correlational design, data were collected from 25 students through an online survey measuring four SRL dimensions cognition, metacognition, social behavior, and motivational regulation—and verified GPA records. Regression analysis revealed a non-significant relationship, with SRL explaining only 1.2% of GPA variance (R Square = 0.012, p = 0.601). These findings suggest that SRL strategies alone are insufficient to predict academic performance and highlight the context-dependent nature of their effectiveness. External factors, such as prior academic achievement, socio-economic status, and institutional support, likely play a more dominant role in influencing GPA. The study acknowledges its limitation in not empirically examining these external factors and calls for future research to explore their mediating or moderating roles. To maximize the effectiveness of SRL, integrating it with additional support mechanisms, such as coaching, technology-enhanced tools, and culturally tailored interventions, is recommended. This study underscores the need for a holistic approach that considers diverse influences on academic success to better address the complexities of student achievement in higher education. Keywords: GPA, self-regulated learning, academic achievement, higher education. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1273-1280